Getting to the CoRe of Collaborative Online International Learning (COIL) - Borger, Jessica Geraldine (Frontiers in Education, 2022)
In response to the COVID-19 pandemic, there was a worldwide pivot of education to online communication and the utilisation of digital technologies to enhance global learning and foster intercultural understanding. Educators faced unprecedented challenges in the conversion of face-to-face interactions into online, virtual classrooms, with many unprepared and untrained. Yet, introduction of online digital technologies for pedagogical interactions expanded the internationalization of previously limited curriculum prospects, creating global interconnectedness with the potential to invoke students’ awareness and appreciation of cultural communication differences. The linked development of international and pedagogical content knowledge (PCK) is key for internationalization of the curriculum. With the growth of new digital communication, learning opportunities such as Collaborative Online International Learning, aims to foster the development of intercultural competencies in our students for future career advancement, yet there remains a tenable lack of available tools for educators to facilitate students actively participating in objective, equitable and inclusive intercultural communication (ICC). Herein, is proposed the novel application of a conceptual tool, a ‘content representation’ or CoRe matrix, which separates a particular topic into divergent, yet linked dimensions of the knowledge and skills attributed to its content, teaching and learning. It is hypothesised the novel application of the CoRe matrix will enhance an educators PCK of ICC, providing the valuable link between international and pedagogical knowledge, for effective internationalization of the curriculum and the development of effective, objective and inclusive student participation in global 21st century classrooms.